The last mirror on the left - Giles, Lamar. 1979- (Giles, L. R. (Lamar R.). Legendary Alston boys adventure, 2021)
Otto and Sheed, The Legendary Alston Boys of Logan County, are ordered by Missus Nedraw to bring a fugitive to justice in a world that mirrors their own but has its own rules.